2022
DOI: 10.1108/heswbl-06-2021-0123
|View full text |Cite
|
Sign up to set email alerts
|

Service learning in Indonesia: developing undergraduate students' leadership during COVID-19 pandemic

Abstract: PurposeThis phenomenological case study reports how 16 participating students built their leadership skill through a community-based service-learning project as a part of their undergraduate program at an Islamic university in Indonesia. Education for sustainability framework promoted by Warwick (2016) was employed to portray students' leadership development and explore their lived experience while doing service-learning project in their neighborhood.Design/methodology/approachPhenomenological case study was e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 35 publications
1
12
0
Order By: Relevance
“…The research conducted by Ferdiansyah et al (2022) and Maulani et al (2022) demonstrated that technological risk influences perceived usefulness. The hypothesis examined in this study is presented as follows:…”
Section: The Influence Of Technological Risk On Perceived Usefulnessmentioning
confidence: 99%
See 2 more Smart Citations
“…The research conducted by Ferdiansyah et al (2022) and Maulani et al (2022) demonstrated that technological risk influences perceived usefulness. The hypothesis examined in this study is presented as follows:…”
Section: The Influence Of Technological Risk On Perceived Usefulnessmentioning
confidence: 99%
“…Perceived ease of use can act as a mediator in the relationship between perceived usefulness and technical risk, according to the findings of direct research conducted by Budiantara et al (2019), Nazirwan (2019), Ferdiansyah et al (2022), andFahazzahrullail (2022). Next, the following is the study's hypothesis: H15: Perceived ease of use mediates the effect of technological risk on perceived usefulness.…”
Section: The Mediating Role Of Perceived Ease Of Use To Increase Perc...mentioning
confidence: 99%
See 1 more Smart Citation
“…The paradigm shifts in achieving such an emergency transition required all the relevant support processes to be conducted through online platform. Remote teaching through an online learning infrastructure involves many complex considerations such as technical arrangement, infrastructure or facilities, and knowledge creation (Ferdiansyah et al, 2022). The key point in developing the digital pathway is the consideration of the instructional design, which is essential to effective transformation the learning environment.…”
Section: Digital Online Accessibility For Emergency Remote Teachingmentioning
confidence: 99%
“…The paradigm shifts in achieving such an emergency transition required all the relevant support processes to be conducted through online platform. Remote teaching through an online learning infrastructure involves many complex considerations such as technical arrangement, infrastructure or facilities, and knowledge creation (Ferdiansyah et al. , 2022).…”
Section: Literature Reviewmentioning
confidence: 99%